2020
DOI: 10.1007/s00484-019-01852-5
|View full text |Cite
|
Sign up to set email alerts
|

Perceived impact of meteorological conditions on the use of public space in winter settlements

Abstract: This study aimed to assess the impact of meteorological conditions on the use of public space in Scandinavia and Canada. Between September 21 and December 18, 2017, a cross-sectional online survey 'EAMQ-Climate: space' was distributed via web-based platforms. Survey responses were received from 361 residents (258 people from Scandinavia and 103 from Canada). The relative impact of the meteorological determinants on the use of public space was calculated, and a factor analysis was performed. Disparities between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Critically, however, not all winter conditions are perceived negatively. Recent research spanning Scandinavia and Canada found that sunshine, snowfall, and snow cover encourage outdoor activity in winter, while darkness, rainfall, and icy or slushy terrain are barriers (Larsson and Chapman 2020). A key implication of this finding is that diverse winter conditions should not be bundled together as an undifferentiated set of problems.…”
Section: Introductionmentioning
confidence: 99%
“…Critically, however, not all winter conditions are perceived negatively. Recent research spanning Scandinavia and Canada found that sunshine, snowfall, and snow cover encourage outdoor activity in winter, while darkness, rainfall, and icy or slushy terrain are barriers (Larsson and Chapman 2020). A key implication of this finding is that diverse winter conditions should not be bundled together as an undifferentiated set of problems.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike visitors who briefly visit these landscapes for recreation, residents/travelers who take longer stays may experience multiple environmental stressors. For instance, snow and ice may make outdoor physical activities very physically and mentally challenging (Chapman et al, 2019;Larsson & Chapman, 2020). Dust may also cause respiratory distress in deserts (Goudie, 2014).…”
Section: Restoring Capacitiesmentioning
confidence: 99%
“…Unlike visitors who briefly visit these landscapes for recreation, residents/travelers who take longer stays may experience multiple environmental stressors. For instance, snow and ice may make physical activities very physically and mentally challenging (Chapman et al, 2019;Larsson & Chapman, 2020). Dust may also cause respiratory distress in deserts (Goudie, 2014).…”
Section: Restoring Capacitiesmentioning
confidence: 99%